2015
DOI: 10.5935/0104-7795.20150034
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged sitting and physical discomfort in university students

Abstract: The evolution of man promoted the adoption of the sitting position for prolonged periods, inducing biomechanical and physiological changes in the body. In an educational setting, adopting this posture can induce musculoskeletal disorders and physical discomfort associated or not with learning. Objective: To quantify and characterize prolonged sitting for college students and to correlate the time spent sitting with complaints of pain and/or discomfort. Method: A qualitative and quantitative study. Data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
3
16
0
1
Order By: Relevance
“…It is in line with the findings from past study that pointed out sitting discomfort will increase from the second minute to the next minute [24]. Furthermore, Caromano et al [25] stated that participants provide the lack of comfort complaints when seating and this condition is increased with time. The next questionnaire is on the overall body part discomfort when seating on the car seat.…”
Section: Subjective Assessment Findingssupporting
confidence: 89%
“…It is in line with the findings from past study that pointed out sitting discomfort will increase from the second minute to the next minute [24]. Furthermore, Caromano et al [25] stated that participants provide the lack of comfort complaints when seating and this condition is increased with time. The next questionnaire is on the overall body part discomfort when seating on the car seat.…”
Section: Subjective Assessment Findingssupporting
confidence: 89%
“…Previous studies found similar findings related to prolonged sitting for study purposes and screen use [8,26,27]. Compared to studies in the rest of the world, we found some different social and environmental factors that promote sedentary behavior, such as cultural aspects, weather conditions, passive transport dependency, and khat consumption.…”
Section: Discussionsupporting
confidence: 72%
“…Regarding students' habits, the majority reported occasional consumption of alcoholic beverages (63.1%), no use of tobacco (88.6%), physical activity practice (35.9%) and having time for leisure occasionally (55.4%). Students' median time of mobile phone use was five daily hours (3)(4)(5)(6)(7)(8)(9)(10), and of the computer was two daily hours (1-4). The median weight of the backpack was 3.1 kg (2.5-4), and the most used means of transportation to go to university was the bus (52.1%).…”
Section: Resultsmentioning
confidence: 99%
“…In their academic routine, health students remain seated for long periods, often in inadequate furniture, develop a large amount of curricular activities and carry heavy materials, which can lead to musculoskeletal overload (8) . In addition, they spend time in health institutions for attending practical classes and internship programs.…”
Section: Introductionmentioning
confidence: 99%